PENDAMPINGAN PENYUSUNAN LAPORAN KEBERLANJUTAN BERBASIS GRI SEBAGAI UPAYA PENERAPAN PRAKTIK BISNIS BERKELANJUTAN PADA UMKM PETERNAKAN SURYA UNGGAS MALANG - Fitriasari, Rizka; Nugraha, Adri Putra (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
MSMEs play an important role in the local economy; however, many MSME actors still lack adequate capacity to systematically document their sustainability practices. This issue is also experienced by Surya Unggas, a poultry farming MSME located in Kidal Village, Tumpang District, Malang Regency, which has implemented several sustainability practices, such as empowering local workers, utilizing local suppliers, and processing livestock waste into organic fertilizer. However, these practices have not yet been documented in a structured sustainability report. This community service activity aims to improve the partner’s understanding and skills in preparing a sustainability report based on the triple bottom line principle and referring to the Global Reporting Initiative (GRI) Standards. The activity employed a participatory mentoring approach through several stages, including initial condition identification, mapping of sustainability practices, training on sustainability concepts and GRI, assistance in report preparation, data validation with the partner, and evaluation of the results. The results of the activity show that the partner was able to prepare its first sustainability report, which includes the MSME profile, sustainability strategy, sustainability governance, economic performance, environmental performance, social performance, and GRI cross-reference index. This activity makes a tangible contribution to improving the partner’s capacity, strengthening business transparency, and positioning the sustainability report as a strategic communication tool for circular economy-based MSMEs.